The importance of distinguishing information from evidence/observations when formulating propositions. Issue 6 (December 2015) - Hicks, T.; Biedermann, A.; de Koeijer, J.A.; Taroni, F.; Champod, C.; Evett, I.W.
Abstract: The value of forensic results crucially depends on the propositions and the information under which they are evaluated. For example, if a full single DNA profile for a contemporary marker system matching the profile of Mr A is assessed, given the propositions that the DNA came from Mr A and given it came from an unknown person, the strength of evidence can be overwhelming (e.g., in the order of a billion). In contrast, if we assess the same result given that the DNA came from Mr A and given it came from his twin brother (i.e., a person with the same DNA profile ), the strength of evidence will be 1, and therefore neutral, unhelpful and irrelevant 1 to the case at hand. While this understanding is probably uncontroversial and obvious to most, if not all practitioners dealing with DNA evidence, the practical precept of not specifying an alternative source with the same characteristics as the one considered under the first proposition may be much less clear in other circumstances. During discussions with colleagues and trainees, cases have come to our attention where forensic scientists have difficulty with the formulation of propositions. It is particularly common to observe that results (e.g., observations) are included in the propositions, whereas—as argued throughout this note—they should not be. A typical example could be a case where a shoe-mark with a logo and the general pattern characteristics of a Nike Air Jordan shoe is found at the scene of a crime. A Nike Air Jordan shoe is then seized at Mr A's house and control prints of this shoe compared to the mark. The results (e.g., a trace with this general pattern and acquired characteristics corresponding to the sole of Mr A's shoe) are then evaluated given the propositions 'The mark was left by Mr A's Nike Air Jordan shoe-sole' and 'The mark was left by an unknown Nike Air Jordan shoe'. As a consequence, the footwear examiner will not evaluate part of the observations (i.e., the mark presents the general pattern of a Nike Air Jordan) whereas they can be highly informative. Such examples can be found in all forensic disciplines. In this article, we present a few such examples and discuss aspects that will help forensic scientists with the formulation of propositions. In particular, we emphasise on the usefulness of notation to distinguish results that forensic scientists should evaluate from case information that the Court will evaluate. Highlights: We show the importance of distinguishing so called 'evidence' from propositions. Forensic observations are to be evaluated by the forensic scientist. They must not be included in propositions that are to be assessed by the Court. We give casework examples across forensic disciplines.